Numerical analysis and parametric study of unreinforced masonry walls with arch openings under lateral in-plane loading. (1st April 2020) - Howlader, M.K.; Masia, M.J.; Griffith, M.C.
Highlights: Finite element modelling (FEM) of perforated unreinforced masonry walls. Wall geometry and vertical pre-compression has significant effect on the behaviour. FEA successfully captured the global in-plane behaviour of the tested walls. Spandrel effect on the global behaviour of the wall is significant. Abstract: This paper presents numerical modelling of the in-plane shear behaviour of unreinforced masonry (URM) walls with a semicircular arch opening. To do so, two dimensional finite element (FE) modelling of a series of experimentally tested walls was conducted using the simplified micro-modelling approach. The models successfully captured the load-displacement behaviour and, to a large extent, the failure modes of the piers and spandrels observed in the experimentally tested walls. The exception was that the FE modelling did not show pier diagonal shear cracking which was observed in some of the tested walls. The model was then used to perform parametric studies to investigate the effect of geometric variations of the walls as well as the effect of vertical pre-compression stresses on the lateral in-plane capacity of the walls. The results obtained from the FE analyses were compared to the anticipated maximum shear strength and the predicted failure modes according to the New Zealand Society for Earthquake Engineering (NZSEE, 2017). From this study, it is shown that there is a significant effect of the wall geometry and vertical pre-compression load on the failure modes and the lateral load resistance capacity of the walls. In most of the cases investigated, the NZSEE equations for maximum shear strength and failure modes agree well with the FEM results. The arch opening was remodelled to a rectangular opening and it was found that the effective pier height for an equivalent rectangular pier adjacent to a semi-circular arched opening can be taken up to the half height of the arch radius.